Risk factors for postoperative thrombosis-related complications in patients undergoing malignant brain tumor resection: a retrospective cohort study - Xiaoyuan Liu; Xingyue Zhang; Tingting Ma; Muhan Li; Liyong Zhang; Shu Li; Min Zeng; Ira S. Kass; Yuming Peng (Frontiers in Neurology, 2023)
IntroductionPatients with malignant brain tumors frequently exhibit hypercoagulation and are at a high risk of postoperative thrombosis-related complications. However, the risk factors for postoperative thrombosis-related complications remain unclear.MethodsIn this retrospective, observational study, we consecutively enrolled elective patients undergoing resection of malignant brain tumors from 26 November 2018 to 30 September 2021. The primary objective of the study was to identify risk factors for a composite of three major adverse events including postoperative lower limb deep venous thrombosis, pulmonary embolism, and cerebral ischemia.ResultsA total of 456 patients were enrolled in this study, where 112 (24.6%) patients had postoperative thrombosis-related complications, 84 (18.4%) with lower limb deep venous thrombosis, 0 (0.0%) with pulmonary embolism, and 42 (9.2%) with cerebral ischemia. In a multivariate model, age more than 60 years (OR: 3.98, 95% CI: 2.30–6.88, P < 0.001), preoperative abnormal APTT (OR: 2.81, 95% CI: 1.06–7.42, P = 0.037), operation duration longer than 5 h (OR: 2.36, 95% CI: 1.34–4.16, P = 0.003), and admission to ICU (OR: 2.49, 95% CI: 1.21–5.12, P = 0.013) were independent risk factors of the postoperative deep vein thrombosis. Intraoperative plasma transfusion (OR: 6.85, 95% CI: 2.73–17.18, P < 0.001) was associated with significantly increased odds of deep vein thrombosis.ConclusionPatients with craniocerebral malignant tumors have a high incidence of postoperative thrombosis-related complications. There is an increase in the odds of postoperative lower limb deep venous thrombosis in patients; over 60 years old, with preoperative abnormal APTT, undergoing surgeries longer than 5-h, admission to ICU, or receiving intraoperative plasma infusion. Fresh frozen plasma infusion should be used more cautiously, especially in patients with a high risk of thrombosis.